F(x) = 2x - 4
f(2 ≤ x) = 2(2 ≤ x) - 4
f(x ≥ 2) = 2(x ≥ 2) - 4
f(x ≥ 2) = 2(x) ≥ 2(2) - 4
f(x ≥ 2) = 2x ≥ 4 - 4
f(x ≥ 2) = 2x ≥ 0
f(x ≥ 2) = x ≥ 0
f(x) = 2x - 4
f(x ≤ 6) = 2(x ≤ 6) - 4
f(x ≤ 6) = 2(x) ≤ 2(6) - 4
f(x ≤ 6) = 2x ≤ 12 - 4
f(x ≤ 6) = 2x ≤ 8
f(x ≤ 6) = x ≤ 4
Answer:
The distributive property of multiplication
Step-by-step explanation:
we know that
The <u>distributive property of multiplication</u> states that the product of a number by a sum, is equal to multiply each addend by the number (This is called distributing the number) and then, you can add the products
so
![a*(b+c)=a*b+a*c](https://tex.z-dn.net/?f=a%2A%28b%2Bc%29%3Da%2Ab%2Ba%2Ac)
in this problem we have
----> the number -3 is distributed
therefore
We have the distributive property of multiplication
Answer:
I hope you get it .............
Answer:
-4(-41)
Step-by-step explanation: